Characteristics of Radio Emissions Associated With Terrestrial Gamma‐Ray Flashes. Issue 7 (25th July 2018) - Mailyan, B. G.; Nag, A.; Murphy, M. J.; Briggs, M. S.; Dwyer, J. R.; Rison, W.; Krehbiel, P. R.; Boggs, L.; Bozarth, A.; Cramer, E. S.; Roberts, O. J.; Stanbro, M.; et al.
Abstract: In this study, we analyze 44 terrestrial gamma‐ray flashes (TGFs) detected by the Fermi Gamma‐ray Burst Monitor (GBM) occurring in 2014–2016 in conjunction with data from the U.S. National Lightning Detection Network (NLDN). We examine the characteristics of magnetic field waveforms measured by NLDN sensors for 61 pulses that occurred within 5 ms of the start‐time of the TGF photon flux. For 21 (out of 44) TGFs, the associated NLDN pulse occurred almost simultaneously with (that is, within 200 μs of) the TGF. One TGF had two NLDN pulses within 200 μs. The median absolute time interval between the beginning of these near‐simultaneous pulses and the TGF flux start‐time is 50 μs. We speculate that these RF pulses are signatures of either TGF‐associated relativistic electron avalanches or currents traveling in conducting paths "preconditioned" by TGF‐associated electron beams. Compared to pulses that were not simultaneous with TGFs (but within 5 ms of one), simultaneous pulses had higher median absolute peak current (26 kA versus 11 kA), longer median threshold‐to‐peak rise time (14 μs versus 2.8 μs), and longer median peak‐to‐zero time (15 μs versus 5.5 μs). A majority (77%) of our simultaneous RF pulses had NLDN‐estimated peak currents less than 50 kA indicating that TGF emissions can be associated with moderate‐peak‐amplitude processes. The lightning flash associated with one of the TGFs in our data set was observed by a Lightning Mapping Array, which reported a relatively high‐power source at an altitude of 25 km occurring 101 μs after the GBM‐reported TGF discovery‐bin start‐time. Key Points: TGF‐associated RF pulses have a wide range of NLDN‐estimated peak currents, which are proportional to their magnetic field peak amplitudes Median rise time and peak‐to‐zero time for TGF‐simultaneous RF pulses were significantly longer than those for nonsimultaneous pulses A TGF that was associated with relatively high‐power VHF radiation is described in detail